KORELASI ANTARA PERHATIAN ORANG TUA DENGAN PRESTASI BELAJAR SISWA KELAS IV SDN SEKARPURO, KAB. MALANG - Supriono Agus Tekege; Heri Setiawan (Program Studi PGSD, FKIP, Universitas Mataram, 2020)
The purpose of this study to determine (1) the learning achievement of fourth grade students of SD Negeri Sekarpuro; (2) The parent's attention Elementary School fourth grade students Sekarpuro; and (3) the relationship between parents' attention to student achievement Sekarpuro Elementary School fourth grade. The data were collected by distributing questionnaires to 41 levels of parental attention fourth grade students of SDN Sekarpuro and retrieve data class IV student achievement based on the SDN Sekarpuro Middle Semester Exam (UTS). Data analysis was performed with data analysis techniques assisted Pearson Product Moment correlation SPSS 2.1 for windows. The result showed that the level of parent,s attention of fourth grade students of SDN Sekarpuro level of attention from their parents as much as 92.7% at the high category, and 7.3% were in the moderate category. Achievement of fourth grade students of SDN Sekarpuro showed excellent criterion 68.3% and 31.7% better. Based on the results of hypothesis testing, after being tested by using SPSS 21 for windws known that r-count of 0661. The analysis results greater than r table for N = 41 with significant level of 5% ie 0,308. Because the value of r count is greater than r table (0.661> 0.308) it can be concluded that the alternative hypothesis (Ha) is received, or in other words there is a significant relationship between parent's attention to student achievement Sekarpuro fourth grade SDN subdistrict of Pakis, District of Malang.